2021
DOI: 10.3389/fbioe.2021.661409
|View full text |Cite
|
Sign up to set email alerts
|

Development, Preparation, and Biomedical Applications of DNA-Based Hydrogels

Abstract: Hydrogels have outstanding research and application prospects in the biomedical field. Among them, the design and preparation of biomedical hydrogels with deoxyribonucleic acid (DNA) as building blocks have attracted increasing research interest. DNA-based hydrogel not only has the skeleton function of hydrogel, but also retains its biological functions, including its excellent selection specificity, structural designability, precise molecular recognition ability, outstanding biocompatibility, and so on. It ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 74 publications
0
14
0
Order By: Relevance
“…Hydrogels and water-soluble gel networks are currently being extensively studied for their use as biocompatible materials. Hydrogels formed with DNA are largely reported in the literature. , Usually, these hydrogels are formed by hybridization of DNA Y-shaped structures or DNA-grafted polymers with a complementary DNA sequence leading to a network. In the current hydrogels, we showed that short sequences with only six units are able to form hydrogels by supramolecular arrangement strongly stabilized by CT of the DAN and NDI pairs.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrogels and water-soluble gel networks are currently being extensively studied for their use as biocompatible materials. Hydrogels formed with DNA are largely reported in the literature. , Usually, these hydrogels are formed by hybridization of DNA Y-shaped structures or DNA-grafted polymers with a complementary DNA sequence leading to a network. In the current hydrogels, we showed that short sequences with only six units are able to form hydrogels by supramolecular arrangement strongly stabilized by CT of the DAN and NDI pairs.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrogel, a 3D polymer composite system consisting of water and cross-linked polymers, can imbibe large quantities of water or biological fluids ( Li et al, 2020b ; Jian et al, 2021 ). With its excellent stability, malleability, biocompatibility and sustained release, hydrogel is an ideal drug carrier for SCI treatment.…”
Section: Empirical Sci Treatment Involving Biomaterial-based Tlr4-nf-...mentioning
confidence: 99%
“…According to the type of hydrogel cross-linking and components, DNA-based hydrogels can be divided into pure DNA-based hydrogels and hybrid DNA-based hydrogels. Pure DNA-based hydrogels are constructed solely using DNA molecules, which are assembled through Watson–Crick or non-Watson–Crick interactions, as well as enzymatic ligation or polymerization. , The latter is formed by connecting the DNA molecules that are grafted onto hydrophilic polymer chains, which function as interaction nodes. , In this review, we focus on the development of recent works on DNA-based hydrogels in bioanalysis and cancer therapeutics applications. Additionally, in order to promote the further development of DNA-based hydrogels, particularly in the field of biosensing, we also provide some insights into the current challenges and future prospects of these materials (Figure ).…”
Section: Introductionmentioning
confidence: 99%